Balloon-Atrioseptostomy in Small Children Using an Embolectomy Catheter: Preliminary Data - R. Dalla Pozza; M. Hermann; N. A. Haas (Case Reports in Cardiology)
Interventional treatment of restrictive atrial septal defects in complex heart disease is considered state-of-the-art therapy up to date. Nevertheless, dedicated balloons are lacking so far, as several products have been withdrawn from the market. We report on off-label use of a balloon embolectomy catheter used successfully in a preterm patient and discuss whether this device might be used in other patients as well as it seems to be promising due to its shape and versatility.